2019
DOI: 10.1021/acs.joc.9b02605
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Insertion Reactions of Silanes with Aryldiazoacetates

Abstract: Si−H insertion reactions represent an important method for the efficient construction of new C−Si bonds, and typically, they are conducted in the presence of metal catalysts. In this report, we describe a photochemical approach that now allows the insertion of carbenes into the Si−H bond of silanes under metal-free reaction conditions (23 examples, up to 83% yield).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
(34 reference statements)
0
28
0
Order By: Relevance
“…Initially, the UV–vis absorbance spectra of 2-diazo-2-phenylacetate 1a and sulfur ylide 2a was conducted and both of the two starting materials presented an absorbance spectrum in the visible region (Scheme a). According to literature reports, both aryl diazoacetates and sulfur ylides could serve as carbene precursors under photo-irradiation. , Then, we conducted some control experiments to identify which substrates were activated under our optimal reaction conditions (Scheme b). It was reported that styrene is an efficient carbene trapping reagent under photochemical conditions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the UV–vis absorbance spectra of 2-diazo-2-phenylacetate 1a and sulfur ylide 2a was conducted and both of the two starting materials presented an absorbance spectrum in the visible region (Scheme a). According to literature reports, both aryl diazoacetates and sulfur ylides could serve as carbene precursors under photo-irradiation. , Then, we conducted some control experiments to identify which substrates were activated under our optimal reaction conditions (Scheme b). It was reported that styrene is an efficient carbene trapping reagent under photochemical conditions .…”
Section: Resultsmentioning
confidence: 99%
“…In the past several decades, carbene generation from diazo compounds under thermal or transition-metal catalytic conditions has been well investigated . Only recently, since 2018, photolysis of aryl diazoacetates under sole visible light irradiation has emerged as a promising new and sustainable approach to initiate free carbene-transfer reactions. , To date, the strategy has been elegantly applied to X–H insertion, cyclopropanation and cyclopropenation, and some other types of reactions . In 2018, Zhou, He, and co-workers developed a blue-light-emitting diode (LED)-promoted cross-coupling of two distinct diazo compounds, leading to trisubstituted alkenes in high yields and stereoselectivities .…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Koenigs et al reported a method for a visible-light-driven insertion reaction of silanes 94 with aryl diazoacetates 1 (Scheme 25). 65 This strategy enables the formation of a vast array of products in moderate to good yields, even for such demanding substrates as triphenyl silane (product 95).…”
Section: -Pyridone C (Scheme 22bmentioning
confidence: 99%
“…On the basis of above experimental results and literature report [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68], a plausible reaction mechanism was proposed in Scheme 3. Initially, visible-light irradiation of aryldiazoacetate resulted in N 2 gas extrusion and generated the reactive carbene species.…”
Section: Rom L-(-)-borneolmentioning
confidence: 87%